Comparing the performance of circulating cathodic antigen and Kato-Katz techniques in evaluating Schistosoma mansoni infection in areas with low prevalence in selected counties of Kenya: a cross-sectional study - Collins Okoyo; Elses Simiyu; Sammy M. Njenga; Charles Mwandawiro (BMC, 2018)
Abstract Background Kato-Katz technique has been the mainstay test in Schistosoma mansoni diagnosis in endemic areas. However, recent studies have documented its poor sensitivity in evaluating Schistosoma mansoni infection especially in areas with lower rates of transmission. It's the primary diagnostic tool in monitoring impact of the Kenya national school based deworming program on infection transmission, but there is need to consider a more sensitive technique as the prevalence reduces. Therefore, this study explored the relationship between results of the stool-based Kato-Katz technique with urine-based point-of-care circulating cathodic antigen (POC-CCA) test in view to inform decision-making by the program in changing from Kato-Katz to POC-CCA test. Methods We used two cross-sectional surveys conducted pre- and post- mass drug administration (MDA) using praziquantel in a representative random sample of children from 18 schools across 11 counties. A total of 1944 children were randomly sampled for the study. Stool and urine samples were tested for S. mansoni infection using Kato-Katz and POC-CCA methods, respectively. S. mansoni prevalence using each technique was calculated and 95% confidence intervals obtained using binomial regression model. Specificity (Sp) and sensitivity (Sn) were determined using 2 × 2 contingency tables and compared using the McNemar's chi-square test. Results A total of 1899 and 1878 children were surveyed at pre- and post-treatment respectively. S. mansoni infection prevalence was 26.5 and 21.4% during pre- and post-treatment respectively using POC-CCA test, and 4.9 and 1.5% for pre- and post-treatment respectively using Kato-Katz technique. Taking POC-CCA as the gold standard, Kato-Katz was found to have significantly lower sensitivity both at pre- and post-treatment, Sn = 12.5% and Sn = 5.2% respectively, McNemar test χ2 m = 782.0, p < 0.001. In overall, the results showed a slight/poor agreement between the two methods, kappa index (k) = 0.11, p < 0.001, inter-rater agreement = 77.1%. Conclusions Results showed POC-CCA technique as an effective, sensitive and accurate screening tool for Schistosoma mansoni infection in areas of low prevalence. It was up to 14-fold accurate than Kato-Katz which had extremely inadequate sensitivity. We recommend usage of POC-CCA alongside Kato-Katz examinations by Schistosomiasis control programs in low prevalence areas.